2009
DOI: 10.1056/nejmoa0900854
|View full text |Cite|
|
Sign up to set email alerts
|

Moderate Hypothermia to Treat Perinatal Asphyxial Encephalopathy

Abstract: Induction of moderate hypothermia for 72 hours in infants who had perinatal asphyxia did not significantly reduce the combined rate of death or severe disability but resulted in improved neurologic outcomes in survivors. (Current Controlled Trials number, ISRCTN89547571.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,198
9
38

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,542 publications
(1,313 citation statements)
references
References 24 publications
35
1,198
9
38
Order By: Relevance
“…On each ROI, the mean value of the resistivity and its standard deviation Effect of Therapeutic Hypothermia (for Hypoxo Ischemic Encephalopathy) and Rewarming on the Cerebral Resistivity As a clinical illustration of the capability of resistivity maps to give easily readable clinical information on the resistivity of the vascular network, serial examinations have been performed on a full-term infant subjected to therapeutic hypothermia after neonatal hypoxo ischemic encephalopathy. 27,28 The patient was maintained under mild whole-body hypothermia (33.51C) from 6 hours of life and for 72 hours. When the period of cooling concluded, rewarming was cautiously conducted and the servocontrolled rectal temperature was allowed to rise by no more than 0.51C per hour, to a maximum of 36.5±0.21C.…”
Section: Quantitative Data Mapping With Ultrafast Doppler Imagingmentioning
confidence: 99%
“…On each ROI, the mean value of the resistivity and its standard deviation Effect of Therapeutic Hypothermia (for Hypoxo Ischemic Encephalopathy) and Rewarming on the Cerebral Resistivity As a clinical illustration of the capability of resistivity maps to give easily readable clinical information on the resistivity of the vascular network, serial examinations have been performed on a full-term infant subjected to therapeutic hypothermia after neonatal hypoxo ischemic encephalopathy. 27,28 The patient was maintained under mild whole-body hypothermia (33.51C) from 6 hours of life and for 72 hours. When the period of cooling concluded, rewarming was cautiously conducted and the servocontrolled rectal temperature was allowed to rise by no more than 0.51C per hour, to a maximum of 36.5±0.21C.…”
Section: Quantitative Data Mapping With Ultrafast Doppler Imagingmentioning
confidence: 99%
“…Rapid initiation of therapeutic hypothermia is optimal since earlier initiation results in better outcomes. 10,11 Cooling on transport is feasible and safe, and results in quicker time to therapeutic temperature than when initiated at the referral center. 12 Although therapeutic hypothermia has significantly improved outcomes among neonates with HIE, the neuroprotective effect is incomplete, with death and severe disability rates at approximately 50% among those who received treatment in the clinical trials.…”
Section: Resuscitation and Supportive Carementioning
confidence: 99%
“…Finally, in the 1990s laboratory studies demonstrated the benefit of mild hypothermia in dogs after cardiac arrest [14]. In the last decade, pivotal randomized clinical trials have provided direct evidence of a benefit of mild hypothermia to improve neurological outcome after cardiac arrest and perinatal asphyxia [1,2,[4][5][6][7].…”
Section: Historical Aspectsmentioning
confidence: 99%
“…Until the last decade, management of a newborn with HIE had consisted largely of supportive care. In the last 6 years, 3 large, randomized, placebo-controlled trials have shown that TH initiated within 6 h of birth reduces death and disability in these infants [5][6][7].…”
Section: Perinatal Asphyxiamentioning
confidence: 99%
See 1 more Smart Citation